Central obesity indicating a higher prevalence of lower urinary tract symptoms: A case‐control matching analysis from a Chinese cross‐sectional study in males. Issue 2 (11th July 2018) - Xie, Lianguang; Chen, Yang; Tan, Aihua; Gao, Yong; Yang, Xiaobo; Mo, Zengnan; Zhang, Haiying
Abstract : Objective: The aim of this study was to explore the association between central obesity and lower urinary tract symptoms (LUTS) among men in southern China, and test the hypothesis that central obesity measured by the waist‐to‐hip ratio (WHR) is a predictor of the severity of LUTS. Methods: In all, 4303 men from the Fangchenggang Area Male Healthy and Examination Survey (FAMHES) were included in this study. LUTS were assessed by the International Prostate Symptom Score (IPSS), whereas central obesity was evaluated by the WHR. The association between WHR and LUTS was tested using logistic and Cox regression analyses. Results: After screening, 2917 participants were in the study. Univariate analysis indicated significant differences in WHR in the presence of LUTS ( P = .012). After stratification by age, logistic regression indicated that LUTS were more frequent in 60‐year‐old men with a higher WHR (odds ratio [OR] 2.89, 95% confidence interval [CI] 1.21–6.89) compared with participants <40 years old. Cox regression analysis after pairing of 252 LUTS cases and 252 control subjects from the 2917 eligible participants according to age (±5 years), indicated that central obesity (WHR ≥0.9) may be significantly associated with moderate or severe LUTS (OR 1.95, 95% CI 1.16–3.26). The associations between central obesity and straining (OR 2.44, 95% CI 1.40–4.24) and weak stream (OR 2.37, 95% CI 1.27–4.45) were significant after multivariate adjustment. Conclusions: Males with central obesity are at increased risk of LUTS, and increased WHR is associated with worsened straining and weak stream. Further investigations are needed to confirm these associations.